Use of a device for bone allograft channeling in an experiment with rabbits: Narrative review - Alexander Rudenko; Berik Tuleubaev; Nurettin Heybeli (National Scientific Medical Center, 2022)
Aim: To investigate the method of antibiotic impregnation of the femoral bone head (prepared according to the Marburg bone bank system) using a patented device designed for uniform channeling followed by deep soaking of the bone graft spongy tissue with drug solutions. Materials and methods: Femoral bone heads prepared according to the Marburg bone bank system and impregnated with gentamicin were used in the experiment. Four groups were formed depending on the impregnation method. A whole femoral head was used in groups I and II, a perforated femoral head - in groups III and IV. In groups I and III, antibiotic impregnation was carried out simultaneously with heat treatment of the femoral heads, in groups II and IV - after heat treatment. The perforated, treated, gentamicin-soaked femoral bone head was compared to the "PerOssal" beads soaked in gentamicin. The degree of influence on the S. aureus strains was determined using the agar diffusion method. Results and conclusion: The results indicate the presence of antimicrobial activity in the antibiotic-impregnated allograft in all groups. However, the growth inhibition zone was lower in groups I and III. The antimicrobial activity of gentamicin in the I and III was lower than in the groups II and IV.  ​An increase in the diffusion of the antibiotic is facilitated by the perforation of the bone allograft according to the developed method using a patented device. It has been established that perforation and soaking of the bone allograft in an antibiotic solution increases the antibiotic impregnation of the bone graft.